ATAMA – SÍRTQÍ KOMPOZICIYANÍŃ BIR BÓLEGI SÍPATÍNDA (Qaraqalpaq povestleri mısalında) - Bekbergenova, Z.U. (ILIM hám JÁMIYET, 2025)
Chapters, parts, titles, epigraphs, prologues, epilogues, etc. occupy an important place in the external composition of prose works. The article examines the role of the title as one of these external compositional tools in shaping the architectonics of a literary work and draws relevant conclusions using the example of contemporary Karakalpak short stories.